Strategi Pemasaran Digital yang Efektif untuk Platform E-commerce - Engla Anggraini; Nur Fitriana (Politeknik Negeri Padang, 2024)
Digital marketing has become the main key in developing and maintaining the success of e-commerce platforms in this digital era. This article presents an in-depth review of effective digital marketing strategies to increase visibility, increase conversions, and build customer loyalty on e-commerce platforms. The study highlights several core strategies, including search engine optimization (SEO) to improve rankings in search results, use of paid advertising (PPC) to instantly increase website traffic, and leveraging social media to build closer relationships with audiences. In addition, this approach also addresses the importance of relevant and high-value content in attracting and maintaining the interest of potential customers. Case analysis of leading e-commerce platforms illustrates the implementation of these practices and their results in enhancing business growth. Discussions about performance measurement and strategy adaptation based on data and the latest market trends are an integral part of this article.